Kansas Field Research 2019 (Kansas Agricultural Experiment Station Research Reports, 2019)
Research from Kansas State University experiment fields on crop varieties, tillage, irrigation, weed management, and fertilizers.
Keywords: corn; soybean; wheat; weed management; management practices